Design And Design Of A Temperature And Humidity Monitoring System For Broiler Chicken Cages Based Internet Of Things (IOT) - Prasetia, Robby Adrian; Dahlan, Andi Ahmad; Lifwarda, Lifwarda (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2024)
In this research, we designed a tool that is used to help chicken farmers to continue their daily activities in raising livestock. Problems often experienced by chicken farmers are frequent theft, and having to check the temperature manually in the coop. So a Security and Temperature Monitoring and Light Control System for Broiler Chicken Cages Based on Internet of Things (IoT) was created using NodeMcu Esp32 as the controller of the entire system. The tools used in this system are, Buzzer, DHT22, LCD 16x2, ESP32, Breadboard, Relay, and Incandescent Lamp. The tool making method uses engineering design methods in making the automation system. The test results show that the system that has been made is able to maintain the temperature in the chicken coop in accordance with the ideal conditions for Broiler chickens.